Influence of weight and structure on biological behavior of polypropylene mesh prostheses placed at the esophageal hiatus - Senft, Jonas; Gehrig, Tobias; Lasitschka, Felix; Linke, Georg R.; Shevchenko, Maxym; Bruckner, Thomas; Kenngott, Hannes Götz; Fischer, Lars; Müller, Beat P. (Journal of laparoendoscopic & advanced surgical techniques, 2014)
Background: Experimental knowledge about mesh behavior at the esophageal hiatus is rare, but such information is essential in order to find a safe and effective method of mesh reinforcement. This study aimed to investigate the influence of mesh structure on the biological behavior of polypropylene prostheses placed at the hiatus.Materials and Methods: Twenty-four pigs in three groups of eight underwent implantation of heavyweight small-porous (HW-SP), heavyweight large-porous (HW-LP), or lightweight large-porous (LW-LP) circular polypropylene mesh at the hiatus. Eight weeks later, the meshes were explanted. Macroscopic analysis was performed evaluating mesh deformation, adhesions, and position relative to the hiatal margin. Histological analysis comprised evaluation of foreign body reaction and tissue integration by mononuclear cell count and immunostaining of Ki-67, collagen type I, and collagen type III.Results: No mesh-related complications occurred. Mesh shrinkage was observed within all groups and was the lowest for HW-LP, higher for HW-SP, and highest for LW-LP (13.8% versus 19.5% versus 25.5%; P<.001). The adhesion score was highest for HW-SP, lower for HW-LP, and lowest for LW-LP (11.0 versus 8.0 versus 6.0; P<.001). The collagen type I/III ratio was higher for HW-SP compared with HW-LP and LW-LP (3.1 versus 2.2 versus 1.8; P=.014).Conclusions: Heavyweight polypropylene meshes may be advantageous for application at the hiatus. They provide a solid fixation of the esophagogastric junction by adhesions, which may contribute to a reduction of hernia recurrence. In heavyweight meshes, the large-porous structure is associated with superior form stability, and small-porous meshes are superior with regard to solidity of tissue integration, which may prevent mesh migration.
Gesehen am 14.08.2020